Pernikahan Beda Agama Dalam Pandangan Agama Buddha - Pratiwi, Virna Dita; Sineru, Wistina; Edi Sumarwan (LPPM UIN Saizu Purwokerto, 2023)
The purpose of this study is to describe interfaith marriage in the view of Buddhism using the literature study method. With the results of the study, namely in the view of Buddhism, the importance of similar beliefs (samma saddha) and religious values is considered a strong foundation for harmony in marriage. But if this cannot be done, then there are no sanctions for Buddhists who carry out these interfaith marriages. Because this is not something that is justified or blamed. In this case, Human Rights Law No. 39 of 1999 which extends to the applicable laws and regulations, namely the Indonesian Marriage Law, Law No. 1 of 1974 and according to the 1st KHI statement of 1974, CLD-KHI states that it does not prohibit interfaith marriages and guarantees freedom and protects the rights everyone to marry and have a family. For this reason, in interfaith marriages, mutual respect, communication of a deep understanding of each other's religious beliefs and practices. This can help in building a strong foundation for cooperation, balance and respect in the marriage relationship.